Basic Psychometric Properties and Italian Normative Data of the DSM-5 Level 2 Anger, Anxiety, and Depression Scales, and DSM-5 Severity of Dissociative Symptoms Scale - Antonella Somma; Arianna De Ciechi; Linda Boscaro; Chiara Arioli; Giulia Gialdi; Valeria Mariani; Andrea Fossati (Mediterranean Journal of Clinical Psychology)
Background: To promote the shift to a dimensional approach to diagnosis, the DSM-5/DSM-5-TR incorporates self-report dimensional measures of DSM-5 cross-cutting symptoms. Against this background, the aim of the present study is examining the basic psychometric properties of the measures and providing clinicians with Italian normative data for the DSM-5 Level 2 Anger, Anxiety, and Depression Scales, and for the DSM-5 Severity of Dissociation Symptoms Scale.